Performance assessment in education for sustainable development: A case study of the Qatar education system - Mona M. Al-Kuwari (14151543) (2021)
Various studies show that sustainability and education are closely interdependent. Design and implementation of the right performance assessment for students’ skills acquisition and achievements is, therefore, critical for achieving the Sustainable Development Goals (SDGs). This article presents an in-depth analysis of the Qatar education system (K-12 level), focusing on the current assessment approaches and remaining challenges that hinder the development and implementation of proper performance-assessment methods aligned with SDGs. Based on a proposed theoretical framework influenced by the constructive alignment theory, this article examines the current performance assessment practices in Qatar and recommends potential improvement avenues with respect to SDGs and education goals (EGs). Using this framework as an analytical tool, results reveal a lack of alignment between the assessment practices, educational goals, and the SDGs. This work shows that tailored, contextually proper, and progressive assessment strategies need to be developed to accurately evaluate and guide the twenty-first-century skills of the students toward the achievement of SDGs. Further findings of this article concern presentation and discussion of the locally relevant and consistent recommendations for performance assessment methodologies that must be redesigned to be compatible, aligned, and supporting the SDGs and EGs. Other Information Published in: PROSPECTS License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s11125-021-09570-w